Tracheal atypical solitary carcinoid in a so called “difficult asthma”: a diagnostic challenge - Martina Turrin; Francesca Maria Pontoriero; Giordano Fiorentù; Giulia Grisostomi; Francesca Zampieri; Francesca Savoia; Cosimo Catino; Giuseppe Zanardi; Piera Peditto; Nicola Malacchini; Fabiola Zeraj; Matteo Bonato; et al. (Monaldi Archives for Chest Disease, 2023)
This report describes the case of a 46-year-old non-smoker housewife. She presented to our attention having a diagnosis of “difficult asthma” from another center in the previous two years. She had no allergies and had not been exposed to an excessive amount of noxious stimuli. Her chronic respiratory symptoms (dyspnea on exertion with wheezing) remained uncontrolled despite maximal anti-asthmatic inhaled therapy. An HRCT scan was performed to further investigate other pulmonary diseases that mimic asthma. It revealed a pedunculated endotracheal lesion with regular borders that obstructed 90% of the tracheal lumen. The lesion was removed via rigid bronchoscopy with laser endobronchial; histological examination revealed the presence of atypical carcinoid. Atypical carcinoids are a rare subtype of neuroendocrine lung tumor that accounts for 2% of all thoracic malignancies. They frequently arise from the central airways and cause obstructive symptoms such as coughing, wheezing, chest pain, or recurrent obstructing pneumonia, which is caused by central airway obstruction. Clinical onset is gradual and characterized by non-specific symptoms, which frequently result in misdiagnosis. As a result, in a young patient with progressive dyspnea, chronic cough, and wheezing that is not responding to anti-asthmatic treatment, second-level investigations are required and may lead to a definite diagnosis, allowing the appropriate course of treatment to begin.